Penyuluhan Tentang Bahaya Limbah Pestisida Untuk Petani - Ahmad Farhan; Novia Rahmawati; Sucipto Adisuwiryo; Ika Wahyu Utami; Larasati Rizky Putri; Yunita Friscila Suryana; Muhawid AL Ken (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Pesticides are all chemicals and other substances, as well as microorganisms and viruses, which are used to eliminate or prevent pests and diseases that damage plants, plant parts or agricultural products. The use of pesticides in the agricultural sector is still widely used even though pesticide prices are increasing every year. Indramayu is one of the largest agricultural lands in West Java, so the majority of Indramayu residents earn their living as farmers. The problem that farmers often encounter in using pesticides is a lack of knowledge and low awareness, which results in a lack of behavior to prevent the consequences of using pesticides, such as a lack of use of personal protective equipment by farmers when spraying with pesticides. The aim of the Community Partnership Program (PKM) is to help increase knowledge and understanding of how to prevent the impact of pesticide use on the farming community in Pawidean Village. This PKM takes the form of assistance, counseling or outreach, showing videos and making posters for farmers. Farmers hope that the results of this PKM will increase farmers' understanding of practices to prevent health impacts caused by the use of pesticides.